100 HTML5 Quiz Questions and Code Solutions with New Features Explained - Svekis, Laurence (Packt Publishing, 2020)
Build the skills and confidence to pass any HTML5 interview and exam with this question-and-answer guide About This Video Become familiar with the latest features of HTML5 Gain the skills to pass any HTML5 interview or exam Learn how to solve common HTML issues In Detail HTML is the standard markup language for formatting documents that are displayed in web browsers. Nowadays, every web developer should know the basics of HTML. But this is still not enough. The latest version of HTML provides several features that are useful to create powerful web applications. This course will test your HTML knowledge and give you a tour of the latest features of HTML5 with the help of interesting questions. All the questions are presented in multiple-choice, and you will have five seconds to answer them. After five seconds, you will be provided with the correct answer, feedback, and details of that answer. In addition to this, code in action examples and content demos related to the questions are also included. How you take the lessons is up to you: you can do them in order or select a random lesson and try your best. You can keep your score separately to track your progress or challenge yourself by questioning. By the end of this course, you will become familiar with the new features of HTML5 and will have discovered new ways to write the HTML code.
Online resource; Title from title screen (viewed December 17, 2020)
Keywords: Streaming video; Internet videos; Vidéo en continu; Vidéos sur Internet; streaming video; Electronic videos